Spermine Significantly Increases the Transfection Efficiency of Cationic Polymeric Gene Vectors - Yue Lv; Jiaoqin Xue; Pengfei Cui; Lin Qiu (Pharmaceutics)
Background/Objectives: Non-viral vectors have gained recognition for their ability to enhance the safety of gene delivery processes. Among these, polyethyleneimine (PEI) stands out as the most widely utilized cationic polymer due to its accessibility. Traditional methods of modifying PEI, such as ligand conjugation, chemical derivatization, and cross-linking, are associated with intricate preparation procedures, limited transfection efficiency, and suboptimal biocompatibility. Methods: In this investigation, enhanced transfection efficiency was achieved through the straightforward physical blending of PEI carriers with spermine. Results: Transfection assays explored the maximal enhancement potential conferred by spermine, alongside further methodological refinements aimed at optimizing transfection efficacy, showcasing a potential increase of up to 40.7%. Through the comparison of different addition sequences of spermine, the optimal complex PEI/Spermine/DNA for transfection efficiency was selected. Characterization of PEI/Spermine/DNA revealed that, compared to PEI/DNA, its particle size increased to approximately 150 nm. Molecular dynamics simulation results revealed that spermine can enhance the interaction between PEI and DNA, thereby forming a system with lower energy and greater stability. Mechanistic inquiries studies also disclosed that spermine augments the endosomal escape capability of PEI carriers without altering pathways involved in the cellular uptake of gene nanoparticles, thereby facilitating heightened gene expression. Conclusions: PEI-Sper emerges as a promising non-viral vector for gene delivery, distinguished by its simplicity in preparation, cost-effectiveness, and superior transfection efficiency.